2014
DOI: 10.3171/2014.9.focus14471
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic laser ablation of high-grade gliomas

Abstract: Evolving research has demonstrated that surgical cytoreduction of a high-grade glial neoplasm is an important factor in improving the prognosis of these difficult tumors. Recent advances in intraoperative imaging have spurred the use of stereotactic laser ablation (laser interstitial thermal therapy [LITT]) for intracranial lesions. Among other targets, laser ablation has been used in the focal treatment of high-grade gliomas (HGGs). The revived application of laser ablation for gliomas parallels major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 79 publications
(143 reference statements)
0
68
0
1
Order By: Relevance
“…6,10 Landmark studies have demonstrated the feasibility and safety of this approach for the treatment of challenging neurooncological lesions that cannot be safely treated via conventional surgical approaches. 2,5,10 Although the procedure has fundamentally reshaped the landscape of neurosurgery, the safety of thermal ablation requires real-time MRI monitoring of thermocoagulation by using a technique called MR thermometry.…”
Section: Neurosurg Focus 41 (4):e7 2016mentioning
confidence: 99%
“…6,10 Landmark studies have demonstrated the feasibility and safety of this approach for the treatment of challenging neurooncological lesions that cannot be safely treated via conventional surgical approaches. 2,5,10 Although the procedure has fundamentally reshaped the landscape of neurosurgery, the safety of thermal ablation requires real-time MRI monitoring of thermocoagulation by using a technique called MR thermometry.…”
Section: Neurosurg Focus 41 (4):e7 2016mentioning
confidence: 99%
“…Several lesion types including epileptogenic foci, tumors, and radiation necrosis have been shown to respond to thermal ablation. 5,6,15,17 Furthermore, LITT has benefited greatly from intraoperative MRI, which allows for real-time monitoring of thermal ablation to ensure conformality of treatment zones. 16 AbbreviAtioNs DBS = deep brain stimulation; EEG = electroencephalography; ICU = intensive care unit; LITT = laser interstitial thermal therapy; mT = microTargeting; TDT = thermal damage threshold.…”
mentioning
confidence: 99%
“…In neurosurgery for example, laser interstitial thermal therapy (LITT) is a preferred treatment option for patients who are not ideal surgical candidates (22). Since their introduction to neurosurgery, lasers have become increasingly safe to use and have been successfully applied for the treatment of unresectable gliomas as well as hard and hemorrhagic tumors such as meniniomas, tumors of the deep skull base, or tumors deep in the ventricles (10,23). Mucosal ablation techniques using lasers are currently being widely and successfully used for the treatment of superficial gastrointestinal cancers including early gastric cancer, superficial esophageal cancer, colorectal adenoma, and high-grade Barrett's esophagus (24).…”
Section: Oncologymentioning
confidence: 99%